Removal of glyphosate on Inceptisols ameliorated with biochar derived from young coconut waste - Moli Monikasari; Arestha Leo Lita; Teguh Budi Prasetyo; Amsar Maulana; Endar Hidayat; Herviyanti Herviyanti (Universitas Sebelas Maret, 2025)
Young Coconut Waste Biochar (YCWB) serves as an ameliorative agent that enhances soil quality and facilitates glyphosate removal, particularly in Inceptisols. This study aimed to evaluate the capacity of Inceptisols enhanced with YCWB to eliminate glyphosate, a commonly used herbicide. Inceptisols amended with 40 t ha⁻¹ YCWB demonstrated an increased surface charge, improving soil properties such as acidity (pH), electrical conductivity (EC), cation exchange capacity (CEC), and soil organic matter (SOM). The adsorption capacity was determined to be 0.87 mg g⁻¹ (or 870.27 mg kg⁻¹) at pH 5.07, under a glyphosate concentration of 100 mg L⁻¹. Glyphosate removal was facilitated by changes in functional groups, as indicated by Fourier-transform infrared spectroscopy (FT-IR), which showed reduced transmittance of O-H, C=C, C-O, C-H, and mineral groups. These modifications indicate an enhancement in the sorption capacity of Inceptisols treated with 40 t ha⁻¹ YCWB. The glyphosate adsorption isotherms followed the sequence: Langmuir > Freundlich model, with performance ranking as soil + 40 t ha⁻¹ YCWB > unamended soil (Inceptisols). The respective R² values were R² = 0.9889 > R² = 0.9739 for the Langmuir model and R² = 0.9953 > R² = 0.9099 for the Freundlich model, confirming a strong interaction relationship (R² > 0.9). This indicates that glyphosate removal occurs through simultaneous or alternating physical and chemical processes. Modifying the surface charge of Inceptisols using biochar-based amelioration technology derived from biomass waste, such as young coconut waste, is critical for improving glyphosate removal efficiency.